1973
DOI: 10.1111/j.1464-410x.1973.tb06815.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Urinary Chemiluminescence of Normal Smokers and Non-smokers and of Patients with Bladder Cancer

Abstract: Summary A relaitively simple procedure th the measurement of urinary chemiluminesece is descirbed and some of the variable affecting such measurmnt are examined. Normal urinary chemiluminescence is due to a low molecular weight and freely dialysible compound. Addition of blood to urine causes chemiluminescence which is not dialysible. Although there was very considerable overlap between the groups, it was found that urinary chemiluminescence was higher in normal smokers than in normal non‐smokers and higher st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1975
1975
1992
1992

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…This study confirms the trends previously reported (Schlegel et al, 1969;Rose and Wallace, 1973). The highest UCLC was in patients with bladder tumours who smoked and the lowest in normal people who were non-smokers (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This study confirms the trends previously reported (Schlegel et al, 1969;Rose and Wallace, 1973). The highest UCLC was in patients with bladder tumours who smoked and the lowest in normal people who were non-smokers (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Many of the physiological variables which can affect UCL have been identified and assessed (Rose and Wallace, 1973), but still there are variations due to sex, diurnal change, diet, drugs, trace elements and perhaps other factors as yet unrecognised that have not been fully evaluated and may cause the wide range of results. The physical capabilities of the biometer and in particular the mixing of the reagents are vital to the intensity of the reaction and may be a major source of error.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations